Shame and social work theory, reflexivity and practice - Frost, Liz 1953-; Magyar-Haas, Veronika; Schoneville, Holger; Sicora, Alessandro (Policy Press, 2020)
Examining experiences of shame and stigma in the context of austerity and the declining welfare state, this book shows how social work can ameliorate the impacts of shame through sensitive, reflective and relationship-based practice. It provides a broad understanding of shame and looks at its impact on both service users and practitioners
Description based on publisher supplied metadata and other sources
Keywords: Electronic books